The role of cerebrospinal fluid levels of neutrophil gelatinase-associated lipocalin (NGAL) and electroencephalography in the assessment of impaired consciousness in the context of infection - Platanaki Christina; Paraskevas Themistoklis; Delastic Anna-Lisa; Michailides Christos; Kantanis Anastasios; Polychronopoulos Panagiotis; Marangos Markos; Velissaris Dimitrios (Sciendo, 2023)
The sepsis syndrome is potentially affecting several organs and systems irrespectively of the primary source of the infection. Alterations of the brain function in sepsis patients may result either from a primary central nervous system (CNS) infection or could be part of the sepsis-associated encephalopathy (SAE), a common complication of sepsis, characterized by a diffuse dysfunction of the brain due to an infection elsewhere in the body without overt CNS infection. Aim of the study was to evaluate the usefulness of electroencephalography and the biomarker neutrophil gelatinase-associated lipocalin (NGAL) when measured in the cerebrospinal fluid (CSF) in the management of these patients.